Graph-based approach for enumerating floorplans based on users specifications. Issue 4 (November 2021) - Shekhawat, Krishnendra; Jain, Rahil N.; Bisht, Sumit; Kondaveeti, Aishwarya; Goswami, Dipam
Abstract: This paper aims at automatically generating dimensioned floorplans while considering constraints given by the users in the form of adjacency and connectivity graph. The obtained floorplans also satisfy boundary constraints where users will be asked to choose their preferred location based on cardinal and inter-cardinal directions. Further, spanning circulations are inserted within the generated floorplans. The larger aim of this research is to provide alternative architecturally feasible layouts to users which can be further refined by architects.